2012
DOI: 10.1097/sla.0b013e3182480a6a
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of Short-Term Clinical Outcomes After Esophagectomy

Abstract: Outcome reporting after esophageal cancer surgery is heterogeneous and inconsistent, and it lacks methodological rigor. A consensus approach to reporting clinical outcomes should be considered, and at the minimum it is recommended that a "core outcome set" is defined and used in all studies reporting outcomes of esophageal cancer surgery. This will allow meaningful cross study comparisons and analyses to evaluate surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
194
0
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(208 citation statements)
references
References 65 publications
6
194
0
8
Order By: Relevance
“…Because neoplastic disease progression in humans appears to be influenced predominantly by severe, as opposed to any septic, complication, selecting an experimental model that reproduces these features was considered imperative. CLP closely approximates the severe septic complications that can occur after a number of gastrointestinal surgeries, including colorectal, gastric, and esophageal oncologic resections (13,20,56). By definition, CLP results in the rapid onset of polymicrobial sepsis with endogenous flora.…”
Section: Figurementioning
confidence: 99%
“…Because neoplastic disease progression in humans appears to be influenced predominantly by severe, as opposed to any septic, complication, selecting an experimental model that reproduces these features was considered imperative. CLP closely approximates the severe septic complications that can occur after a number of gastrointestinal surgeries, including colorectal, gastric, and esophageal oncologic resections (13,20,56). By definition, CLP results in the rapid onset of polymicrobial sepsis with endogenous flora.…”
Section: Figurementioning
confidence: 99%
“…The complications reported for this type of surgery are pneumonia in 2 -39 %, anastomotic leakage in 0 -35 % and recurrent paresis in 0 -31 % (15). Post-operative mortality also varies from one study to the next, and ranges from 0 -15 % (15,16).…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the incidence of post-operative complications and mortality after oesophageal resection in different studies is challenging because standardised complication definitions and grades are not used (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Cervical anastomotic complications of oesophagectomy have been the problem of thoracic surgeons for a long time. Many different hand-suture techniques, such as monolayer or multilayer suture, nonabsorbable or absorbable suture lines and intermittent or continuous suture, have been used, but a high incidence rate of anastomotic leakage reaching 10 to 27 % is still observed [13][14][15]. In this study, seven cases showed anastomotic leakage, but all these cases were cured after conservative treatment, and no operative death occurred [16].…”
Section: Discussionmentioning
confidence: 99%